The relationship between the key sectors in the european union economy and the intra-European Union trade - Martha Alatriste-Contreras (Journal of Economic Structures, 2015)
The paper studies the properties of the productive structure of a region and national economies within the region. We use input-output data to calculate and compare input-output linkages and complex network measures of centrality to identify the most important sectors. We found that the most important sectors in each country are also the most important sectors in the European Union as a whole. Moreover, these sectors are the most intra-European Union traded goods and services. Finally, we computed the effect of a sectoral shock and its diffusion throughout the economy. We found that the most central sectors have the best diffusion of the effect of a shock and also a high aggregate impact in the economy. This gives evidence that centrality measures provided additional information that allowed to identified key sectors that have high linkages and good diffusion of effects. Therefore, the computation of centralities provides an alternative method to identify key sectors and formulate economic policies, complementing input-output analysis.
Keywords: C67; O52; L14; 330; Intersectoral linkages; Productive structure; Centralities